Environmental and monopolistic issues in industrial minerals mining - Aleksandr K Kirsanov; Georgij S Kurchin; Natalia A Shkaruba; Natalia V Nikolaeva; Ravil Z Nafikov; Sergey S Kostilev; Umarjon R Teshaev (Brawijaya University, 2023)
The paper discusses the environmental impact of industrial minerals mining. Research shows that interest in mining of industrial minerals increases year by year, and their demand and consumption will steadily grow. The market conditions are favorable for developing new fields. Both opencast and underground mined minerals are most popular these days. The industrial minerals market analysis indicates its dynamics, but the high monopoly degree of mining of certain minerals causes some restrictions on free competition in subsoil use. At the same time, environmental issues raised at the level of world power governments are not reflected in legislative documents. We raise the possibility of partial transition from opencast mining to underground one-as an alternative that carries environmental improvement of a mining area.